Critical perspectives on predictive policing anticipating proof? - Galis, Vasilis; Gundhus, Helene Oppen 1969-; Vradis, Antonis (Edward Elgar, 2025)
Taking a critical approach, this book advances understanding of the social, legal and ethical aspects of digitalisation in law enforcement and the reliance on data-driven tools to predict and prevent crime. It shows how the proliferation of data analytics challenges citizens’ rights, at a time when what counts as ‘safety’ or ‘policing’ is being fundamentally transformed.